UJI TOKSISITAS (Brine Shrimp Lethality Test) DAN AKTIVITAS ANTIOKSIDAN DARI DAUN SINTRONG (Crassocephalum Crepidioides) DENGAN METODE 2,2-diphenyl-1-picrylhidrazil (DPPH) - Fiktor Boni Pasilala; Daniel Tarigan; Chairul Saleh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2016)
The phytochemical test, brine shrimp lethality test and antioxidant activity test on secondary metabolits of terap (Artocarpus odoratissimus B.) leaves has been completed. The leaves samples are extracted by masseration method that is concentrated by using rotary evaporator. The total extract are fractioned with n-hexane and ethyl acetate. Based on secondary metabolits phytochemical test of terap (Artocarpus odoratissimus B.) leaves showed that total extract and Ethyl Acetat fraction extract contains alkaloids, phenolics, flavonoids, saponins, steroids and triterpenoids. N-hexane fraction extract contain alkaloids, steroids and tritepenoids. In brine shrimp lethality test, the increase larvae death data was recorded and processed using SAS Probit Analysis to determine the Lethal Concentration 50 % (LC50) value. The results of this test showed that the most active extract is metanol extract with LC50 value of 88.0227 ppm. Based on the antioxidant activity by scavenging activity of DPPH used spectrophotometry was obtained that Inhibition Concentration 50% (IC50) of total extract is 369.0833 ppm, extract of n-hexane fraction is 1532.267 ppm and extract of ethyl acetat fraction is 82.89003 ppm.